The impact of gendered organizational systems on women’s career advancement - O’Neil, Deborah A.; Hopkins, Margaret M. (Frontiers in Psychology, 2015)
In this Perspective article we propose that in order to pave the way for women's career advancement into the senior ranks of organizations, attention must be directed at the systemic norms and structures that drive the gendered nature of the workplace. A focus on individual level issues, i.e., women lacking confidence and women opting out, detracts from the work that must be done at the organizational level in order to dismantle the system of pervasive, structural disadvantage facing women seeking to advance to senior leadership positions.